Optimizing Restaurant Tax Supervision In Jakarta: A Case Study Of The Tanah Abang Area - Badruzzuhad, Muhammad Taufiq; Firmansyah, Amrie (WIM Solusi Prima, 2024)
This research aims to explain the business process of supervising the restaurant tax collection in DKI Jakarta. This research also aims to provide suggestions to optimize supervising the restaurant tax collection in DKI Jakarta. The approach used in this research is a qualitative approach with descriptive methods. The data collection in this study was done using the techniques of observation, interview, and documentation study. The results of this study are an explanation of the general description of the restaurant tax collection supervision business process such as monitoring the payment of periodic restaurant tax deposits, comparison of third-party CMS data with internal restaurant taxpayer data, comparison of restaurant tax periodic deposit payment data with similar taxpayers (benchmarking), and implementation of silent operations to taxpayers business premises. This research also produced a proposal in the form of a method to optimize restaurant tax collection supervision activities in DKI Jakarta, especially in Tanah Abang area, namely by using tax data integration between central and local taxes, which is the result of cooperation between DKI Jakarta Provincial Government and the Directorate General of Taxes of the Ministry of Finance of the Republic of Indonesia. This research has several contributions, namely this research supplements the literature regarding the supervision of local tax collection, especially restaurant tax in Indonesia. In addition, the results of this study can also be used by DKI Jakarta Regional Revenue Agency (Bapenda DKI Jakarta) in the formulation of policies on the supervision of local tax collection, especially restaurant tax.